2016
DOI: 10.1515/jppr-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Original Article. An evaluation of some eco-friendly biopesticides against Bemisia tabaci on two greenhouse tomato varieties in Egypt

Abstract: Th is study has two main approaches. First, it exploits the susceptibility of tomato cultivars as a prophylactic measure to detect auto resistance characters of the tested tomato varieties against Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae). Secondly, it evaluates the effi cacy of diff erent bio-rational insecticides against B. tabaci under greenhouse conditions. Th e results exhibited a special signifi cance in B. tabaci infestation suitability between the two tomato varieties with a high infestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“…e result was similar to the application of different strains of B. bassiana, M. anisopliae, and neem extract that reduced 85% to 92% of nymphs from the Srijana tomato variety in Nepal [57] and 50 to 90% reduction in adult whitefly populations on two tomato varieties (Shifa and Savera) in Egypt under greenhouse conditions [58]. Furthermore, Ghongade and Sangha (2021) reported that the application of entomopathogenic fungal isolates of B. bassiana, M. anisopliae, and L. lecanii (1 × 10 9 CFU/ml), neem product (Neem Baan 1% W/W), and chemical pesticide (Malathion 50EC with 4 ml/l) significantly reduced nymphs (82 to 99%) and adults (57 to 98%) of whiteflies on cucumber under greenhouse condition after 3 rd spray application in India [59].…”
Section: Discussionsupporting
confidence: 69%
“…e result was similar to the application of different strains of B. bassiana, M. anisopliae, and neem extract that reduced 85% to 92% of nymphs from the Srijana tomato variety in Nepal [57] and 50 to 90% reduction in adult whitefly populations on two tomato varieties (Shifa and Savera) in Egypt under greenhouse conditions [58]. Furthermore, Ghongade and Sangha (2021) reported that the application of entomopathogenic fungal isolates of B. bassiana, M. anisopliae, and L. lecanii (1 × 10 9 CFU/ml), neem product (Neem Baan 1% W/W), and chemical pesticide (Malathion 50EC with 4 ml/l) significantly reduced nymphs (82 to 99%) and adults (57 to 98%) of whiteflies on cucumber under greenhouse condition after 3 rd spray application in India [59].…”
Section: Discussionsupporting
confidence: 69%
“…Suggestions put forward in studies related to the pesticide spinosad were wide-ranging, especially when it came to sucking insect pests such as whiteflies, (17) discovered the biopesticide spinosad most active in decreasing whitefly density. (18) record in study to evaluate impact of both the pesticide spinosad and the pesticide metarhizium anisopliae, Beauveria bassiana, and azadirachtin in whitefly population density (Bemisia tabaci) ,the high effectiveness of the pesticide spinosad in combating whiteflies population on tomato, compartion to the rest of the biological factors and that the population density of the insect was reduced in all treatments to an extent it ranges between 50% and 94.61% In other research to evaluation of the biocides spinosad and azadirachtin on eggs and nymphs and adults of the whitefly (Bemisia tabaci) in laboratory and greenhouses (19) arrived to these pesticides have an significant effect and there is a clear reduction in fertility, egg hatching, and emergence. also causes great mortalities in nymphs and adults of the whitefly, and the pesticide Azadirachtin has superior effect on the pesticide spinosad.…”
Section: Table (1)mentioning
confidence: 99%
“…En la actualidad existen productos insecticidas de nueva generación, como el Flupyradifurone, el cual es de baja toxicidad para la mayoría de los insectos benéficos, en especial para polinizadores, y bajo riesgo para la salud humana, con lo cual satisface los requerimientos actuales de los insecticidas modernos necesarios para los programas de manejo integrado de plagas (Nauen et al, 2015); así como productos orgánicos con capacidad de controlar las poblaciones de este insecto vector, como lo son los hongos entompatógenos (Abdel-Razek et al, 2017;Stansly y Natwick, 2009) y así reducir el porcentaje de plantas con virosis. El objetivo de este trabajo es identificar nuevas estrategias de control de mosca blanca, vector de enfermedades virales en chile.…”
Section: Introductionunclassified